Perancangan Aplikasi Kasir Toko Happy Fun Cake & Dessert Berbasis Website Menggunakan Metode Waterfall - Reyfany Khaeratulnisa Martadianty; Risah Subariah (CV. Shofanah Media Berkah, 2025)
Happy Fun Cake is a culinary business that sells various Indonesian cakes, desserts, and so on. It is known that the payment recording system at Happy Fun Cake & Dessert is experiencing difficulties and still uses a manual recording system. Therefore, a website-based cashier application must be built that can handle the problems that occur so that it can satisfy both customers and the owner of Happy Fun Cake & Dessert. Due to these problems, the author created a cashier application to facilitate web-based transactions and recording using the waterfall method and PHP as the programming language and MySQL as the maintenance database so that paper media (manual) are not needed. The research findings are expected to facilitate the owner in tracking the store's income and expenses, while the cashier is useful in providing fast and accurate service.